Solitary plantar basal cell carcinoma - Maura Simonetti Junqueira Bourroul; Ludmila Lopes Trindade; Vanessa Soares do Nascimento; Anderson da Costa Lino Costa; Ubirajara Honorato da Silva (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Basal cell carcinoma is the most frequent skin cancer, generally located in hair-bearing, sunlight-exposed areas. Basal cell carcinoma usually occurs on the head and neck, but very rarely on extra-facial locations. We report a case of a 65-year-old woman presenting with a solitary non-healing ulcer on the sole of the right foot for two years. Histopathological examination showed a typical nodular basal cell carcinoma, confirmed by positivity to Ber-EP4 on immunohistochemistry. There was no history of trauma, exposure to noxious agents, basal cell nevus syndrome, or xeroderma pigmentosum.